PENGARUH KOMPETENSI, KEPUASAN KERJA, PARTISIPASI ANGGARAN DAN MOTIVASI TERHADAP KINERJA PERANGKAT DESA DI KABUPATEN DEMAK - Pranata, Yudha; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2024)
This study aims to analyze the factors affecting the performance of village officials in Demak Regency. The independent variables used in this research are competence, job satisfaction, budget participation, and work motivation, while the dependent variable is the performance of village officials. This study employs motivation theory to generate testable hypotheses, and the testing of these hypotheses results in empirical findings.This research uses primary data with a population of 243 village officials. Using the Slovin formula, a sample size of 152 village officials was obtained. The data collection technique is a survey with a questionnaire as the instrument. The method of analysis used in this study is multiple linear regression analysis.The results of this study indicate that competence and job satisfaction have a negative and significant effect on the performance of village officials, budget participation does not have a significant effect on the performance of village officials, and work motivation has a positive and significant effect on the performance of village officials. The variables of competence, job satisfaction, budget participation, and work motivation simultaneously affect the performance of village officials by 10.6%.